Dental Procedures and the Risk of Infective Endocarditis. Issue 43 (October 2015) - Chen, Pei-Chun; Tung, Ying-Chang; Wu, Patricia W.; Wu, Lung-Sheng; Lin, Yu-Sheng; Chang, Chee-Jen; Kung, Suefang; Chu, Pao-Hsien
Abstract : Supplemental Digital Content is available in the text Abstract : Abstract: Infective endocarditis (IE) is an uncommon but potentially devastating disease. Recently published data have revealed a significant increase in the incidence of IE following the restriction on indications for antibiotic prophylaxis as recommended by the revised guidelines. This study aims to reexamine the basic assumption behind the rationale of prophylaxis that dental procedures increase the risk of IE. Using the Longitudinal Health Insurance Database of Taiwan, we retrospectively analyzed a total of 739 patients hospitalized for IE between 1999 and 2012. A case-crossover design was conducted to compare the odds of exposure to dental procedures within 3 months preceding hospitalization with that during matched control periods when no IE developed. In the unadjusted model, the odds ratio (OR) was 0.93 for tooth extraction (95% confidence interval [CI] 0.54–1.59), 1.64 for surgery (95% CI 0.61–4.42), 0.92 for dental scaling (95% CI 0.59–1.42), 1.69 for periodontal treatment (95% CI 0.88–3.21), and 1.29 for endodontic treatment (95% CI 0.72–2.31). The association between dental procedures and the risk of IE remained insignificant after adjustment for antibiotic use, indicating that dental procedures did not increase the risk of IE. Therefore, this result may argue against the conventional assumption on which the recommended prophylaxis for IE is based.